2011
DOI: 10.1103/physrevlett.106.087002
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Superconducting Transition Temperature ofBaSi2by Structural Tuning

Abstract: We present a joint experimental and theoretical study of the superconducting phase of the layered binary silicide BaSi2. Compared with the layered AlB2 structure of graphite or diboride-like superconductors, in the hexagonal structure of binary silicides the sp 3 arrangement of silicon atoms leads to corrugated sheets. Through a high-pressure synthesis procedure we are able to modify the buckling of these sheets, obtaining the enhancement of the superconducting transition temperature from 4 K to 8.7 K when the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 28 publications
4
23
0
Order By: Relevance
“…Moreover, this consistency has also been reported in the analogous Ir 0.94−x Rh x Se 2 . Actually, density functional theory (DFT) and phonon spectrum calculations on tellurium 16 and BaSi 2 17 have pointed out that the increase in T c is closely correlated with an enhancement of EPC strength due to the emergence of the soft phonon mode.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this consistency has also been reported in the analogous Ir 0.94−x Rh x Se 2 . Actually, density functional theory (DFT) and phonon spectrum calculations on tellurium 16 and BaSi 2 17 have pointed out that the increase in T c is closely correlated with an enhancement of EPC strength due to the emergence of the soft phonon mode.…”
Section: Resultsmentioning
confidence: 99%
“…The excellent agreement between our experimental and theoretical results allowed us to not only reconcile previous unexplained anomalies, but also to shed light onto the complex behavior of metastable phases under pressure. Elemental phosphorus, like other elements [53] and compounds [54], has the tendency to form many polymorphs that differ substantially in their electronic and superconducting properties and can coexist in metastable forms over different pressures. In this work, we showed that many of these exhibit critical temperatures which are distinctively higher than the putative ground-state structures.…”
Section: Discussionmentioning
confidence: 99%
“…Application of high pressure represents a promising route for yielding novel materials with often unusual bonding patterns and exceptional physical properties 15. Special interest of experimental and theoretical research groups is motivated by the frequent occurrence of superconducting properties in binary phases of metals with group IV elements.…”
Section: Introductionmentioning
confidence: 99%